Stunting Prevention in the Preconception Period - Wizia, Lady; Yusrawati, Yusrawati; Meinapuri, Malinda; masrul, masrul; Yetti, Husna; Afdal, Afdal (LPPM Universitas Prima Nusantara Bukittinggi, 2024)
Background: The stunting rate in Indonesia in 2022 was 21.6%. I was reduced when compared to the SSGI data in 2021 of 24.4%. The stunting rate appears to be decreasing from year to year, but a joint commitment is still needed to achieve the target of reducing stunting to 14% by 2024. Stunting prevention is a much more effective step than stunting treatment itself. Prevention of stunting can be done by optimizing the role of mothers in the golden phase of child development. stunting prevention in Indonesia still focuses on pregnancy and toddlers, while prevention during the preconception period is still limited.Purpose:To synthesize and critically effective steps that can be taken to prevent stunting in the preconception periodMethods:The research method employed was a literature review, conducted by using primary studies from PubMed, google scholar, and ScienceDirect with the keywords “stunting; prevention; praconception” published between 2017-2023, in English, open access, and relevant to the topicResults:A total of 397 research articles were screened for eligibility, and 15 articles met the inclusion criteria. Based on the 15reviewed articles, devide into three themes: Nutritional status during preconception, Supplementation during preconception and Lifestyle during preconceptionConclusion: This review found that there are several efforts made in preventing stunting in the preconception period. it is recommended that health workers can optimize the prevention of stunting in the preconception period.